Annular bone growth in phalanges of five Neotropical Harlequin Frogs (Anura: Bufonidae: Atelopus) - Lindquist, Erik; Redmer, Michael; Brantner, Emily (Phyllomedusa: Journal of Herpetology, 2012)
Skeletochronological studies were conducted on museum specimensrepresenting five species of the highly threatened Neotropical genus Atelopus (Bufonidae).We detected annular bone growth (expressed as lines of arrested growth [LAGs]) patternsin each species, and this might provide insight to understand demographic constituency infuture studies. In four of the five species under consideration, LAG counts in fore and hindlimb bone occurred in a 1:1 ratio, indicating that bone growth was consistent within eachindividual. The use of skeletochronology in understanding historic and existing populationsof Atelopus might assist in situ and ex situ population managers in making informedstrategic conservation plans.